Intermittent Fasting- A Paradigm Shift In Cancer Prevention and Treatment: A Scoping Review - Khan, Dr. Mohd. Maruf; Mishra, Akanksha (Indonesian Journal of Cancer, 2025)
Background: Cancer, a dreadful disease, is one of the most prominent and prevalent causes of mortality across the globe. The well-being of every human society is impacted by this serious issue. Intermittent fasting has gained popularity due to its potential in enhancing the efficacy of cancer treatment and limiting its detrimental effects.Method: The literature review focuses on illuminating its beneficial role, suggesting that Intermittent fasting has the transformative potential to work as a complementary approach to cancer prevention and treatment.Results: It has been observed that fasting can protect normal cells from the damaging effects of chemotherapy while stimulating the regeneration in normal tissues.Conclusion: By elucidating its mechanisms of action and summarizing current evidence, this scoping overview aims to inform future research directions and clinical guidelines in the pursuit of improved outcomes for cancer patients.